Beneficial effect of soy isoflavones and soy isoflavones plus soy protein on serum concentration of C-reactive protein among postmenopausal women: An updated systematic review and meta-analysis of randomized controlled trials. (June 2021) - Hariri, Mitra; Ghasemi, Ahmad; Baradaran, Hamid Reza; Mollanoroozy, Ensieyh; Gholami, Ali
Highlights: Soy isoflavones could not significantly change serum concentration of CRP among postmenopausal women. The combination of soy isoflavones and soy protein could not significantly change serum concentration of CRP among postmenopausal women. Subgroup analysis based on the most studied variables could not change non-significant results in this study. Abstract: Background: Scientists suggest that soy isoflavones or the combination of soy isoflavones and soy protein may have beneficial effects on inflammation. Thus, the present study aims at conducting a systematic review and meta-analysis on randomized controlled trials (RCTs) in which the effect of soy isoflavones and the combination of soy isoflavones and soy protein on serum concentration of C-reactive protein (CRP) among postmenopausal women is assessed. Methods and materials: A literature searching was done to identify a breadth of related references in PubMed, Scopus, ISI Web of Science, Cochrane Library, and Clinicaltrials.gov up to December 2020. The mean change from baseline in the CRP concentrations and its standard deviation (SD) for both intervention and comparison groups were used to calculate the effect size. The summary of the overall effects and heterogeneity was estimated by using the DerSimonian and Laird random effects model. The protocol was registered in PROSPERO (No. CRD42020166053). Results: This study considered 23 articles for systematic review and 19 articles for meta-analysis. The overall effect presented a non-significant effect of soy isoflavones on serum CRP concentrations (WMD = 0.08 mg/L, 95 % CI: -0.08, 0.24; p = 0.302) and the overall effect of the combination of soy isoflavones and soy protein indicated non-significant effect in serum levels of CRP (WMD= -0.02 mg/L 95 % CI: -0.12, 0.08; p = 0.715). Conclusion: Published RCTs did not provide strong evidence regarding beneficial effect of soy isoflavones or the combination of soy isoflavones and soy protein on serum CRP concentration among postmenopausal women.